OPTIMIZING GROUP PRESENTATION TASK THROUGH PARTICIPATORY EVALUATION - Ratih, Koesoemo (Universitas Muhammadiyah Surakarta, 2008)
Teaching large classes often produces a lot of problems. One of the efforts to minimize the problems is by empowering the students in the learning process. One of the teaching techniques that can empower learners is a group work presentation task. Hence, the objective of this paper is to share a discussion that can be used to optimize the application of a group work presentation task. To get the optimal result, an action research is conducted. Two cycles are applied. The data are taken by observing the learning process when an action is applied, by interviewing the learners involved and by discussing the results with the collaborators. The research shows that group work presentation task can work well when participatory evalu- ation is applied.Â Key word: Group Presentation Task, Participatory Evaluation, and cycle.Â Â